Changes in Foliage Nutrient Composition and Soil Properties in Different Age Classes of Acacia nilotica (L.) Willd Plantation - Singh, G.; Singh, Bilas (Indian Forester, 2007)
Multi-Purpose Tree (MPT) species are extensively planted along Indira Gandhi Canal passing through Indian desert to meet the increasing demand for fuel and fodder and to protect the canal from windblown sand deposition. Soil in and foliage of different aged stand of Acacia nilotica (L.) Willd, planted along the Indira Gandhi Canal area, in Western Rajasthan were analysed with a view to study nutrient build up and the impact of Acacia nilotica plantation on soil properties. Five available stands representing different age classes viz., 4 years (Y4), 7 years (Y7), 9 years (Y9), 12 years and 19 years (Y19). Foliage nutrients varied significantly with stand age. The level of N and K increased showing positive correlation with stand age. P and other foliage nutrient did not show significant correlation. K, Ca, Mg, Cu, Zn, Fe and Mn increased up to Y12. However, some of the nutrients decreased after Y12, particularly in Y19. Soil organic matter increased influencing soil pH, which decreased with stand age. Increased soil organic matter and available nitrogen (NH4-N + NO3-N) in plantation areas indicated greater return as compared to absorption in the form of litter and release of N through mineralization. The decrease in PO4, Ca, Mg and K availability with increasing stand age is indicative of the fertiliser management in latter age of the stand. Cu, Fe, Zn and Mn increased with stand age except Zn and Mn, which were low in Y19 stand. The accumulation of nutrients was more in upper 0-7 cm layer than 7-30 cm layer. The study suggested an increase in SOM and N under A. nilotica plantation; however, a decrease in concentration of some of the nutrients indicates that plantation requires silvicultural management like fertiliser application and or thinning of the stand after 12 year.